A Single Vaccination of Chimeric Bivalent Virus-Like Particle Vaccine Confers Protection Against H9N2 and H3N2 Avian Influenza in Commercial Broilers and Allows a Strategy of Differentiating Infected from Vaccinated Animals - Sun, Yi-xue; Li, Zheng-rong; Zhang, Peng-ju; Han, Jin-hong; Di, Hai-yang; Qin, Jia-yi; Cong, Yan-long (Frontiers in Immunology, 2022)
H9N2 and H3N2 are the two most important subtypes of low pathogenic avian influenza viruses (LPAIV) because of their ongoing threat to the global poultry industry and public health. Although commercially available inactivated H9N2 vaccines are widely used in the affected countries, endemic H9N2 avian influenza remains uncontrolled. In addition, there is no available avian H3N2 vaccine. Influenza virus-like particles (VLPs) are one of the most promising vaccine alternatives to traditional egg-based vaccines. In this study, to increase the immunogenic content of VLPs to reduce production costs, we developed chimeric bivalent VLPs (cbVLPs) co-displaying hemagglutinin (HA) and neuraminidase (NA) of H9N2 and H3N2 viruses with the Gag protein of bovine immunodeficiency virus (BIV) as the inner core using the Bac-to-Bac baculovirus expression system. The results showed that a single immunization of chickens with 40μg/0.3mL cbVLPs elicited an effective immune response and provided complete protection against H9N2 and H3N2 viruses. More importantly, cbVLPs with accompanying serological assays can successfully accomplish the strategy of differentiating infected animals from vaccinated animals (DIVA), making virus surveillance easier. Therefore, this cbVLP vaccine candidate would be a promising alternative to conventional vaccines, showing great potential for commercial development.